2015
DOI: 10.3839/jabc.2015.015
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation Characteristics and anti-Helicobacter pylori Activity of Aqueous Broccoli Fermented by Lactobacillus plantarum MG208

Abstract: Helicobacter pylori infection causes gastrointestinal diseases such as chronic gastritis, peptic ulcers, and may lead to gastric cancer. Several studies have reported that lactobacilli present on broccoli show inhibitory activity against H. pylori. Here, we evaluated aqueous broccoli, fermented by Lactobacillus plantarum MG208, for its fermentation characteristics and anti-H. pylori activities including antibacterial activity, growth inhibition, antiadhesion, and urease inhibition. The results indicated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The construction of a recombinant Lactiplantibacillus plantarum strain expressing the SARS-CoV-2 spike protein can be used as a promising food-grade oral vaccine candidate against SARS-CoV-2 infection [ 15 ]. Yang et al [ 16 ] conducted a study on the effects of aqueous fermented broccoli on the chronic inflammation of the gastrointestinal tract, including gastritis, ulcers, and gastric tumors induction by the Helicobacter pylori bacteria. They showed that the presence of Lactiplantibacillus plantarum bacilli inhibits the growth of Helicobacter bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The construction of a recombinant Lactiplantibacillus plantarum strain expressing the SARS-CoV-2 spike protein can be used as a promising food-grade oral vaccine candidate against SARS-CoV-2 infection [ 15 ]. Yang et al [ 16 ] conducted a study on the effects of aqueous fermented broccoli on the chronic inflammation of the gastrointestinal tract, including gastritis, ulcers, and gastric tumors induction by the Helicobacter pylori bacteria. They showed that the presence of Lactiplantibacillus plantarum bacilli inhibits the growth of Helicobacter bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the presence of Lactiplantibacillus plantarum bacilli inhibits the growth of Helicobacter bacteria. The fermented broccoli using the Lactiplantibacillus plantarum MG208 strain may constitute a functional diet for the treatment of Helicobacter pylori infections [ 16 ]. Mousavi et al [ 17 ] confirmed that the rate of glucose transformation is faster than fructose to lactic acid transformation by Lactiplantibacillus plantarum .…”
Section: Introductionmentioning
confidence: 99%